2007
DOI: 10.1007/s12105-007-0006-5
|View full text |Cite
|
Sign up to set email alerts
|

Plasmablastic Lymphoma of Head and Neck: Report of Two New Cases and Correlation with c-myc and IgVH Gene Mutation Status

Abstract: Plasmablastic lymphoma (PBL) is a rare acquired immunodeficiency syndrome-associated nonHodgkin's lymphoma (AIDS-NHL), with predilection for the mucosa of oral cavity. It usually has a plasmablastic morphology, expressing plasma cell-associated antigens with weak or absent expression of B-cell-associated markers. To further define the immunophenotypic and molecular genetics of these tumors, we investigated two cases of plasmablastic lymphomas of the head and neck for c-myc gene rearrangement and immunoglobulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
0
11
0
1
Order By: Relevance
“…After an extensive search of the English‐language literature, we found 85 PBL cases with available MYC rearrangement information . The detailed clinicopathological data of the 85 cases from the literature are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After an extensive search of the English‐language literature, we found 85 PBL cases with available MYC rearrangement information . The detailed clinicopathological data of the 85 cases from the literature are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…described the first reported cytogenetic abnormality in PBL, an IGH – MYC translocation. In the past few years, several other studies have reported MYC translocations in PBL . However, these reports have included only isolated cases or a small series of tumours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Se trata de un subtipo de linfoma células B caracterizado por un comportamiento clínico agresivo. Este tipo de linfoma se observa con mayor frecuencia en la cavidad oral de pacientes VIH-positivos6, aunque también se puede observar en sitios extra-orales en pacientes VIH-negativos, donde el virus de Epstein-Barr (EBV) puede estar estrechamente relacionado con su patogénesis (2). El PBL representa un reto diagnóstico dada su morfología muy característica y la falta de expresión de CD20, y también un desafío terapéutico, con primeras respuestas a la terapia, pero con altas tasas de recaída y mal pronóstico (3).…”
Section: Introductionunclassified
“…t(8;14)(q24;q32)/MYC-IGH has been described in a subset of plasmablastic lymphomas, but their prevalence needs better definition[54]. Human herpes virus type 8 (HHV8) is absent.Molecular analysis of plasmablastic lymphomas has shown that most cases have monoclonal IGH rearrangements, but a subset show somatic mutations of the IGH variable regions, indicating derivation from post-germinal center B-cells.…”
mentioning
confidence: 99%